Interactions between DMPC Liposomes and the Serum Blood Proteins HSA and IgG - Sabín Fernández, Juan Daniel (2009)
The interaction between two serum blood proteins, namely human serum albumin (HSA) and human immunoglobulin G (IgG), with 1,2-dimyristoyl-sn-glycero-3-phosphatidylcholine (DMPC) liposomes has been studied in detail using dynamic light scattering, flow cytometry, enzyme-linked immunosorbent assay (ELISA), electrophoretic mobility, differential scanning calorimetry (DSC), and surface tension measurements. HSA and IgG interact with liposomes forming molecular aggregates that remain stable at protein concentrations beyond those of total liposome coverage. Both HSA and IgG penetrate into the liposome bilayer. An ELISA assay indicates that the Fc region of IgG is the one that is immersed in the DMPC membrane. The liposome−protein interaction is mainly of electrostatic nature, but an important hydrophobic contribution is also present.